(untitled) (El-Wahat Journal for Research and Studies, 2025)
This study was designed to determine the post-prandial blood glucose of four commonly used cultivars of dates (“Ghars"; "Deglet Nour" ; "Degla Beida"; "Addela") in healthy subjects and their effects on glycemic index. This research also aims to explore the possibility of consumption of these cultivars of dates by obese and diabetics. These cultivars were chosen on the basis of their consumption enhanced by the local population. Composition analysis was carried out for four types of dates. The weights of the flesh of the date’s equivalent to 50 g of available carbohydrates (7 to 8 dates) were calculated. The study subjects were twenty eight volunteers (non-diabetic) with a mean age of 22.14 ± 0.134 years. Each volunteer was tested on five separate days with 50 g of glucose (reference food) and 50 g equivalent of available carbohydrates from the 4 cultivars of date. Capillary glucose was measured in volunteers at 0, 15, 30, 45, 60, 90 and 120 min. The post-prandial response was recorded by using MATLAB program. The glycemic index was determined as ratios of the incremental areas under the response curves for the dates compared to glucose. Mean glycemic index of the dates were 43.27±14.05, 52.22±9.82, 53.95±23 and 42.11±14.05 for Ghars, Deglet Nour, Degla Beida and Addela, respectively. There were statistically significant differences in the GI between the four cultivars of dates. The results show low glycemic indices for the four types of dates included in the study and that their consumption by healthy individuals does not result in significant postprandial glucose excursions. These findings point to the potential benefits of dates for diabetic subjects when used in a healthy balanced diet. Key words: Dates; Glycemic Index, diabetes, obesity, Algeria